1341 Contribution of workplace psychosocial factors on neck and shoulder symptoms among manufacturing workers. (24th April 2018) - Shiao, Judith; Lin, Kuan-Fen; Chu, Po-Ching; Chen, Chih-Yong; Liu, Li-Wen; Pan, Yi-Tsong; Guo, Leon
Abstract : Introduction: Neck and shoulder pain is a common complaint in workplaces, due to a combination of exposure to ergonomic and psychosocial factors. Information is relatively lacking on the contribution of workplace psychosocial factors to neck and shoulder symptoms. This investigation aimed to determine the contribution of workplace justice and job insecurity to neck and shoulder pain among manufacturing workers in Taiwan. Methods: A cross-sessional survey on a representative sample of employed workers were conducted in 2010. Those employed in manufacturing industries were included for this analysis. The adopted Chinese version of the Nordic Musculoskeletal Questionnaire was used to assess musculoskeletal symptoms. Self-reported neck and shoulder pain affecting work performance was considered the positive outcome. Self-reported ergonomic factors, workplace justice, and job insecurity were assessed by using previously validated instruments. General linear model was used to obtain relative risk (RR), and population attributable risk (PAR) was estimated. Result: Among the 24 427 participants completing the questionnaire, 8632 worked in manufacturing industries. Among them, 1291 (15%) complained of neck/shoulder pain affecting work performance. After adjusting for age, in men (5839, 68%), repeated hand monotonous motion (RR=1.32, 95% CI: 1.24 to 1.40), inappropriate work desk/chair height (RR=1.49, CI: 1.36 to 1.62), prolonged use of computers (RR=1.10, CI: 1.02 to 1.19), and low workplace justice (RR=1.53, CI: 1.40 to 1.68) were significant factors for neck/shoulder pain. The PARs for these factors were 6.5%, 19.7%, 1.9%, and 11.7%, respectively. In women, inappropriate work desk/chair height (RR=1.60, CI: 1.43 to 1.76), low workplace justice (RR=1.49, CI: 1.33 to 1.67), and job insecurity (RR=1.10, CI: 1.01 to 1.22) were significant factors. The PARs were 13.2%, 7.6%, and 2.0%, respectively. Discussion: Among manufacturing workers, neck/shoulder pain is related to psychosocial factors. The PAR of around 10% for these factors are lower than ergonomic factors, but should not be ignored when workplace strategies are to be developed to prevent musculoskeletal symptoms.